Treatment of Patellofemoral Pain Syndrome with Dielectric Radiofrequency Diathermy: A Preliminary Single-Group Study with Six-Month Follow-Up - Manuel Albornoz-Cabello; Cristo Jesús Barrios-Quinta; Isabel Escobio-Prieto; Raquel Sobrino-Sánchez; Alfonso Javier Ibáñez-Vera; Luis Espejo-Antúnez (Medicina, 2021)
Background and Objectives: Notwithstanding patellofemoral pain syndrome (PFPS) being one of the most common causes of pain in the front of the knee in outpatients, few studies have shown the effects of radiofrequency on knee pain and function in this population. The aim of the present study was to determine whether outpatients diagnosed with PFPS obtained improvement in pain and function after treatment by dynamic application of monopolar dielectric diathermy by emission of radiofrequency (MDR). Materials and Methods: An experimental study was conducted with 27 subjects with PFPS. Subjects were treated with 10 sessions of MDR in dynamic application. The visual analogue scale (VAS), the Kujala scale, the DN4 questionnaire, the lower extremity function scale (LEFS), the range of movement (ROM) in knee flexion and extension and the daily drug intake were measured pre- and post-intervention and at the time of the follow-up (six months). Results: Statistically significant differences were found in pain perception (VAS: F1,26 = 92.43, p < 0.000, ŋ2 = 0.78 and DN4: F1.26 = 124.15, p < 0.000, ŋ2 = 0.82), as well as improvements in functionality (LEFS: F1.26 = 72.42, p < 0.000, ŋ2 = 0.74 and Kujala: F1.26 = 40.37, p < 0.000, ŋ2 = 0.61]) and in ROM (Flexion: F1.26 = 63.15, p < 0.000, ŋ2 = 0.71). No statistically significant changes in drug intake were found. Conclusions: The present study shows that the dynamic application of MDR seems effective in reducing pain and increasing functionality and knee flexion in patients with PFPS, after a follow-up of six months.